ChemInform Abstract: High‐Temperature Synthesis of Amides from Alcohols or Aldehydes by Using Flow Chemistry. Issue 16 (April 2015) - Ambreen, Nida; Wirth, Thomas
Abstract An efficient and fast conversion of aliphatic and aromatic alcohols or aldehydes into the corresponding primary amides is successfully achieved at high temperatures by using flow chemistry.